The Neurocognitive Basis for Impaired Dual-Task Performance in Senior Fallers - Nagamatsu, Lindsay S.; Hsu, C. Liang; Voss, Michelle W.; Chan, Alison; Bolandzadeh, Niousha; Handy, Todd C.; Graf, Peter; Beattie, B. Lynn; Liu-Ambrose, Teresa (Frontiers in Aging Neuroscience, 2016)
Falls are a major health-care concern, and while dual-task performance is widely recognized as being impaired in those at-risk for falls, the underlying neurocognitive mechanisms remain unknown. A better understanding of the underlying mechanisms could lead to the refinement and development of behavioural, cognitive, or neuropharmacological interventions for falls prevention. Therefore, we conducted a cross-sectional study with community-dwelling older adults aged 70-80 years with a history of falls (i.e., two or more falls in the past 12 months) or no history of falls (i.e., zero falls in the past 12 months); n = 28 per group. We compared functional activation during cognitive-based dual-task performance between fallers and non-fallers using functional magnetic resonance imaging (fMRI). Executive cognitive functioning was assessed via Stroop, Trail Making, and Digit Span. Mobility was assessed via the Timed Up and Go test. We found that non-fallers exhibited significantly greater functional activation compared with fallers during dual-task performance in key regions responsible for resolving dual-task interference, including precentral, postcentral, and lingual gyri. Further, we report slower reaction times during dual-task performance in fallers and significant correlations between level of functional activation and independent measures of executive cognitive functioning and mobility. Our study is the first neuroimaging study to examine dual-task performance in fallers, and supports the notion that fallers have reduced functional brain activation compared with non-fallers. Given that dual-task performance – and the underlying neural concomitants – appears to be malleable with relevant training, our study serves as a launching point for promising strategies to reduce falls in the future.